Little Women - Alcott, Louisa May (Cairo dar kitab for publishing, 2024)
The story known for initiating a genre of family stories for children, explores themes of love, duty, and personal ambition with Jo march often at the emotional center, the novel has inspired numerous adaptations, including film in 1933, 1994, and greta greta gerwing's acclaimed version in 2019
1
Keywords: English fiction